’Provintia Lakedemonie’ and Laconian Chamareti in 1204: A New Perspective on ‘Partitio Romanie’ - KOSKINAS, Aristotelis (Byzantina Symmeikta, 2025)
The Fourth Crusade document known as Partitio Romanie outlines a partition of the Byzantine Empire but omits several imperial provinces. N. Oikonomides proposed that these territories were seditiously distanced from the short-lived regime imposed by the Crusaders in Constantinople in 1203. Provintia Lakedemonie, a province of Lacedaemonia attested only in this document and arguably the power-base of a Laconian “tyrant” named Chamaretus, provides a case-study particularly apposite for resuming this discussion, focusing on a range of multifarious problems assessed by Oikonomides.